New PD-L1 inhibitors in non-small cell lung cancer – impact of atezolizumab - Seetharamu N (Dove Medical Press, 2017)
Nagashree Seetharamu, Isabel R Preeshagul, Kevin M Sullivan Monter Cancer Center, Hofstra-Northwell Health School of Medicine, Lake Success, NY, USA Abstract: The era of immunotherapy has changed the face of how we approach treatment for many oncologic and hematologic malignancies. Lung cancer has been in the forefront of checkpoint inhibition for the past 2 years and has paved the path for other subspecialties. While PD-1 inhibitors nivolumab and pembrolizumab have been approved for non-small cell lung cancer (NSCLC), this review focuses on atezolizumab, its landmark studies, and ongoing trials. Atezolizumab is the first programmed death ligand 1 (PD-L1) inhibitor to receive US Food and Drug Administration (FDA) approval for metastatic NSCLC patients who have progressed on frontline chemotherapy. This approval was based on two open-label Phase II multicenter trials, POPLAR (NCT01903993) and BIRCH (NCT02031458). Both studies revealed a benefit in overall survival (OS), progression-free survival, and response rate in the atezolizumab arm when compared to single-agent docetaxol. There were also fewest Grade 3–5 treatment-related adverse events (TRAEs) in the atezolizumab cohort. The open-label randomized Phase III OAK trial (NCT02008227) further established the role of atezolizumab in previously treated NSCLC. This study compared atezolizumab with docetaxel in patients with advanced NSCLC (squamous or nonsquamous histologies) who had progressed on one to two prior chemotherapy regimens. OS in the PD-L1-enriched population was superior in the atezolizumab arm (n=241) at 15.7 months compared with docetaxel (n=222) at 10.3 months (hazard ratio [HR] 0.74, 95% confidence interval [CI] 0.58–0.93; p=0.0102). Patients lacking PD-L1 also had survival benefit with atezolizumab with a median OS (mOS) of 12.6 months versus 8.9 months with chemotherapy (HR 0.75, 95% CI 0.59–0.96). Benefit was noted in both squamous and nonsquamous NSCLC subsets and regardless of PD-L1 expressivity. As seen in the POPLAR and BIRCH studies, the toxicity profile was significantly better with immunotherapy. The future is unfolding rapidly as new checkpoint inhibitors are gaining FDA approval. It is still not known if these agents will be used in combination with chemotherapy, with other immune-modulating agents, radiation therapy, or all of the above. The results of these studies investigating their use in combination with chemotherapy agents, with other immunotherapy agents such as CTLA-4 inhibitors, and with radiation therapy, are eagerly awaited. Keywords: PD-1, PD-L1, ADCC, CDC,checkpoint inhibition